(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate neonatal outcomes in cases of fetal growth restriction from 37 weeks of gestation at Hanoi Obstetrics and Gynecology Hospital. Objects and Methods: A prospective cross-sectional descriptive study was conducted on 139 pregnant women at ≥37 weeks of gestation diagnosed with fetal growth restriction. Neonatal outcomes were followed up and evaluated in infants born to mothers admitted for management and pregnancy termination at Hanoi Obstetrics and Gynecology Hospital. Results: Increasing gestational age was associated with a lower birth weight percentile (p < 0.05). The mean birth weight was 2320 ± 153.2 g. One neonatal death was recorded (0.7%), occurring in the group with a birth weight percentile below the 3rd percentile. The proportion of neonates with a 1-minute Apgar score <7 was 3.6%, while the rate at 5 minutes was 0.7%. The most common neonatal complications were respiratory distress and neonatal infection, each accounting for 6.5%. NICU admission was required in 28.1% of neonates. Abnormal umbilical artery Doppler findings were significantly associated with an increased risk of a 1-minute Apgar score <7 (p < 0.05). A cerebroplacental ratio (CPR) ≤1 was significantly associated with an increased risk of NICU admission (p < 0.05). Conclusion: Appropriate timing of delivery in fetal growth restriction is essential to minimize adverse neonatal outcomes, including respiratory distress and neonatal mortality. The cerebroplacental ratio and umbilical artery Doppler assessment provide important clinical information for identifying fetal compromise, supporting delivery timing decisions, and prognosticating postnatal neonatal outcomes.